First signs of torture in Italy: A probable case of execution by the wheel on a skeleton from 13th century Milano. (September 2019) - Mazzarelli, Debora; Gibelli, Daniele; Mattia, Mirko; Bertoglio, Barbara; Sguazza, Emanuela; Fedeli, Anna Maria; Cattaneo, Cristina
Abstract: Although the issue of torture and capital punishment has been addressed in the forensic literature, very few articles have addressed similar cases in archaeological or historical scenarios even if some do provide interesting data for what concerns human violence in general. This report aims at presenting a case of the skeleton of a male, aged between 17 and 20 years, recovered from the archaeological site of S. Ambrogio in Milan and dating back to the Middle Ages (1290–1430). The anthropological and osteological analyses highlighted symmetrical multiple perimortem fractures of ulnae, radii, tibiae and fibulae both on the right and left side. In addition, signs of decapitation were found on the occipital bones. Evidence from the anthropological and historical analyses led to the hypothesis of an execution by the wheel, a specific type of torture at that time. This case describes for the first time the remains of a victim of the wheel and underlines the importance of archaeology and anthropology in reconstructing cases of violation of human rights in the past. Highlights: Violent death in Medieval Milano recorded on the remains of a young male. First case of torture of the wheel identified in Italy on skeletal remains. Case of interpersonal violence representing an event of social marginalization.